Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Rewrite the quadratic formula and discriminant expression for clarity and proper formatting.

[tex]\[
x = \frac{-b + \sqrt{b^2 - 4ac}}{2a}
\][/tex]

[tex]\[
b^2 - 4ac
\][/tex]


Sagot :

Certainly! Let's go through the quadratic formula and the calculation of the discriminant step-by-step.

A quadratic equation is generally expressed in the form:
[tex]\[ ax^2 + bx + c = \0 \][/tex]

The quadratic formula for solving this equation for \( x \) is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2-4ac}}{2a} \][/tex]

To use this formula, we first need to calculate the discriminant, which is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]

The discriminant helps us determine the nature of the roots of the quadratic equation:
1. If \(\Delta > 0\), the equation has two distinct real roots.
2. If \(\Delta = 0\), the equation has exactly one real root (a repeated root).
3. If \(\Delta < 0\), the equation has two complex roots.

Let's assume \( a = 1 \), \( b = 1 \), and \( c = 1 \). These are the coefficients of the quadratic equation.

Step-by-Step Solution:

1. Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (1)^2 - 4 \cdot 1 \cdot 1 \][/tex]
[tex]\[ \Delta = 1 - 4 \][/tex]
[tex]\[ \Delta = -3 \][/tex]

2. Determine the type of roots based on the discriminant (\(\Delta\)):
Since \(\Delta = -3\), which is less than 0, the quadratic equation will have two complex roots.

3. Use the quadratic formula to find the roots:
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]

Since \(\Delta\) is negative, we will end up with an imaginary part in our solution.

Plugging in the values, we get:
[tex]\[ x = \frac{-1 \pm \sqrt{-3}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-1 \pm i\sqrt{3}}{2} \][/tex]

4. Express the roots:
The two roots are:
[tex]\[ x_1 = \frac{-1 + i\sqrt{3}}{2} \][/tex]
[tex]\[ x_2 = \frac{-1 - i\sqrt{3}}{2} \][/tex]

So, the solutions to the quadratic equation \( x^2 + x + 1 = 0 \) are:
[tex]\[ x_1 = \frac{-1 + i\sqrt{3}}{2} \][/tex]
[tex]\[ x_2 = \frac{-1 - i\sqrt{3}}{2} \][/tex]

And the discriminant is [tex]\(\Delta = -3\)[/tex]. These are the detailed steps and the final solutions for the quadratic equation using the given coefficients.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.